Difficulties in identifying the bacterial species from the genus Clostridium in a case of injury-related osteitis - Kierzkowska, Marta; Pędzisz, Piotr; Babiak, Ireneusz; Janowicz, Jakub; Kulig, Mateusz; Majewska, Anna; Sawicka-Grzelak, Anna; Młynarczyk, Grażyna (Folia microbiologica, 2018)
Most Clostridium species are part of saprophytic microflora in humans and animals; however, some are well-known human pathogens. We presented the challenges in identifying the Clostridium species isolated from a patient with an infected open dislocation of the proximal interphalangeal joint of the fourth digit of the right hand. The clinical materials were intraoperative samples collected from a patient diagnosed with an injury-related infection, with soft tissue loss and tendon sheath involvement. The available biochemical, molecular, and genetic techniques were used in identifying the isolated bacteria. The isolated bacterium was shown to have low biochemical activity; hence, it was not definitively identified via biochemical tests Api 20A or Rapid 32A. Vitek 2 and mass spectrometry methods were equally inconclusive. Clostridium tetani infection was strongly suspected based on the bacterium's morphology and the appearance of its colonies on solid media. It was only via the 16S rRNA sequencing method, which is non-routine and unavailable in most clinical laboratories, that this pathogen was excluded. Despite appropriate pre-laboratory procedures, which are critical for obtaining reliable test results, the routine methods of anaerobic bacterium identification are not always useful in diagnostics. Diagnostic difficulties occur in the case of environment-derived bacteria of low or not fully understood biological activity, which are absent from databases of automatic bacterial identification systems.
Keywords: dospělí; Clostridium; mikrobiální testy citlivosti; Metronidazole; Adult; DNA bakterií; Reproducibility of Results; RNA, Ribosomal, 16S; DNA, Bacterial; shluková analýza; lidé; Sensitivity and Specificity; Anti-Bacterial Agents; Clindamycin; klindamycin; senzitivita a specificita; Humans; Microbial Sensitivity Tests; reprodukovatelnost výsledků; Male; metronidazol; osteitida; mužské pohlaví; Poland; Cluster Analysis; antibakteriální látky; RNA ribozomální 16S; Osteitis; Polsko